Study on feeding practices of infants among the mothers in selected villages, at Dhamrai. - Karim, Mohoshina; Farah, Shayela; Ferdousi, Jannatul (Journal of Dhaka National Medical College & Hospital, 2013)
Infants are the most vulnerable group among all the groups in our society. Infants constitute about 3% of the total population of Bangladesh. About 1 new born comes to the earth per 11 seconds in Bangladesh. Breastfeeding of infants is an essential health and medical decision for both the mother and her baby. Breastfeeding results in significant health gain, obesity reduction and cost saving to society. Breastfeeding decisions and practices are influenced by multiple factors including knowledge, attitudes and beliefs, as well as socio-cultural and physiological factors. This was a rural based cross sectional descriptive study carried out among 320 villagers of selected villages, at Dhamrai upazilla health complex, Dhaka provides information about breast feeding practices & awareness regarding usefulness of it from 7th December to 30th December 2011. Result shows, 48.1% of the respondents were from the age group of 21-25 years. The mean age of the respondents was 25.34 yrs & SD = ± 4.281. About half of the respondents 151(47.2%) had primary education & 96(30%) had secondary education. Most of the respondents 301(94.1%) were housewife, 14(4.4%) were service holder and 5(1.6%) were agriculture worker. The mean monthly family income of the respondents was 7626.56±3171.248 Taka. Out of 320 respondents about 137(42.8%) of the responding mothers continued breast feeding to their babies for 9-12 months and 239 (91.6%) weaned their babies at correct times that means within 6 months of life. The present study showed that most mothers 315(98.4%) were aware about the usefulness of breast feeding, we found 218 (68.1%) had the knowledge of starting weaning food. The present study was done in selected villages of Dhamrai, covering a small group of population which does not represent the whole nation. Therefore, a large scale community based study is needed to know the real situation of the country DOI: http://dx.doi.org/10.3329/jdnmch.v18i2.16020 J. Dhaka National Med. Coll. Hos. 2012; 18 (02): 30-36